Luzes sobre o direito português : os projetos de Códigos de Direito Criminal e de Direito Público de Pascoal José de Mello Freire dos Reis (1738-1798) - Sofia Alves Valle Ornelas (2015)
The work analyses the diversity of the Juridical Enlightenment and its mediations in the Portuguese context of the second half of the eighteenth century. After analysing the various meanings of this movement were investigated its possible repercussions in the juridical framework. Among them, it is emphasized that the Illustrated Right, even in the seventeenth century, rebuilt the sense of natural law in a more humanistic and rational perspective. The laws also were organized in systematic codes of deductive rationally. From these considerations the Illustrated Right, addressed the controversial situation of the Portuguese eighteenth-century reality under the Reformism Illustrated. Regarding the legal knowledge, Portugal met with strong inspiration from the Enlightenment materialized by Law of Good Reason (1769), the curricular restructuring of the Law School in Coimbra University (1772) and the projects legal codes from Pascoal José de Mello Freire dos Reis (1738-1798). Thus, the Enlightenment and its appropriations about Right in Portugal were in vogue as in other parts of Europe in the modern period.